Cybersecurity in the Internet of Things: Securing the Connected World - Yakubu, Abubakar Lidani (Faculty of Natural and Applied Sciences Journal of Computing and Applications, 2024)
IoT introduces a new dawn of device interconnectivity, changing the way in which devices communicate and share information with each other. This sort of technological advancement often comes with a significant rise of cybersecurity threats, bringing major problems to the reliability of the IoT bionetwork as a whole. The study's aim is to propose a solution which will help in mitigating the risk of cybersecurity threats in IoT, classifying those types of threats into physical manipulation/malware and data breaches. In other to curve these threats, it is necessary to take a multi-layered security approach, effective management practice, and device-level security. The security measures discussed include authentication and management policy. However, constant challenges of some primary authentication processes such as weak passwords, inadequate secure communications protocols, interoperability issues, and lack of secure data storage have brought the need for this research. Artificial intelligence, blockchain, and cloud computing provide a promising opportunity to reinforce security in IoT. In the quest for a safer IoT future, this study underlines the significance of collective teamwork and partnership. The study also highlights the criticality of more robust security measures in IoT bionetwork. A call to action echoes through the study by urging researchers and stakeholders to come together in other to address those threats by embracing the evolving nature of technological advancement in other to ensure the secure progression of the IoT future. Collaborating together through shared knowledge in other to bring a more secure network as well as to straighten the future of the IoT network foundation for the continuation and the growth of the IoT bio connectivity.